Changes of spermatogenesis rates and pampiniform plexus draining vein among newly diagnosed varicocele patients and recurrent ones - N. G. Osipov; N. P. Teplinskaya; Yu. A. Sobolenko; G. I. Alexeychuk (Андрология и генитальная хирургия, 2014)
The article touches upon the results of comparative evaluation of spermatogenesis disorder rates and haemodynamic changes of venous basins involved in pampiniform plexus drain among 34 newly diagnosed and recurrent varicocele patients. The essential role of left internal spermatic vein at development and maintenance of varicose transformation of pampiniform plexus veins is emphasized. The interaction of spermatogenesis change rates and haemodynamic changes of left internal spermatic vein is revealed. The limitations of diagnosis of clinically developed diagnostic phlebography are demonstrated through clinical examples during search of venous outflow through external spermatic vein and during evaluation of iliac vein haemodynamic changes. The possible reasons provoked expansion of varicocele false relapse are stated.